Професор П.П. Копняєв – вчений, громадський діяч, організатор вищої електротехнічної освіти (до 150-річчя зі дня народження) - Клепіков, В.Б.; Тверитникова, О.Є. (Електротехніка і електромеханіка, 2017)
Розкрито процес зародження системи вищої електротехнічної освіти в Україні наприкінці ХІХ ст. початку ХХ ст.
Обґрунтовано внесок професора П.П. Копняєва у заснування наукової електротехнічної школи України. Розкрито організаційну діяльність вченого у створенні електротехнічного факультету Харківського політехнічного інституту
та першого в Україні спеціалізованого вищого навчального закладу електротехнічного профілю. Доведено, що вісім
основних електротехнічних напрямів наукових досліджень, започаткованих П.П. Копняєвим, набули розвитку і стали
в подальші роки окремою науковою школою або науковим напрямом. Раскрыто процесс зарождения системы высшего электротехнической образования в Украине в конце XIX в. начала
ХХ в. Обоснованно вклад профессора П.П. Копняева в основание научной электротехнической школы Украины. Раскрыто организационную деятельность ученого в создании электротехнического факультета Харьковского политехнического института и первого в Украине специализированного высшего учебного заведения электротехнического
профиля. Доказано, что восемь основных электротехнических направлений научных исследований, начатых
П.П. Копняевым, получили развитие и стали в последующие годы отдельной научной школой или научным направлением Purpose. To carry out complete historical and scientific analysis of Professor P.P. Kopniaiev's activities and establish his
role and place of achievements in the formation of the basic
concepts and directions of the theory of electrical engineering
and its practical application in the development of higher education in Ukraine. Methodology. We have applied general
scientific methods of logic and classification, analysis and
synthesis and special historical methods – historicalcomparative, problem-chronological, synchronic and diachronic. Results. On the basis of generalization of a wide
range of sources of central, regional and personal archives,
the principles and content of scientific-pedagogical, organizational and public activities of P.P. Kopniaiev were revealed
and the classification of the scientific work according to the
main directions of his research was conducted. Originality.
Complex analysis of P.P. Kopniaiev's scientific-pedagogical,
organizational and public activities were carried out in the
field of higher electrical engineering education and industrial
development in Ukraine, and his scientific achievements were
classified according to the main directions. Practical value.
Factual information, generalizations and conclusions can be
applied in the teaching of humanitarian and engineering disciplines in higher education, in particular in the development
of the lecture courses and textbooks used in educational activities, as well as in the preparation of general and scientific
works on the history of science and technology.